Short Communication: Phylogenetic analysis and molecular identification of Canar (Smilax spp.) in Java, Indonesia Based on DNA Barcoding Analysis - LULUT DWI SULISTYANINGSIH; MARLINA ARDIYANI; ABINAWANTO ABINAWANTO; ANDI SALAMAH (Biodiversitas Journal of Biological Diversity, 2018)
Sulistyaningsih LD, Abinawanto, Ardiyani M, Salamah A. 2018. Short Communication: Phylogenetic analysis and molecular identification of Canar (Smilax spp.) in Java, Indonesia Based on DNA Barcoding Analysis. Biodiversitas 19: 364-368. Smilax spp. (Smilacaceae) has long been used as medicinal herbs especially in East Asia and North America as they were known to be rich in steroidal saponin. Pharmacological study has been carried out in Indonesia. This genus is widespread in Indonesia and fairly abundant in Java and has been known either as edible fruit or medicinal plants. Characteristics of Smilax as a dioecious plant with high morphological variations make it thorny in species identification. Various molecular approaches have been devised to overcome identification problems such as DNA barcoding. This study, therefore was conducted to analyze the DNA barcoding application for phylogenetic and identification of Smilax in Java. A total of 31 samples were used in this study including 19 accession numbers from NCBI GeneBank. The genus Ripogonum was used as the out-group in phylogenetic reconstruction. Samples were successfully extracted by CTAB method with some modifications. rbcL region was used as the DNA barcode showed sufficient variation and conserved flanks. Two unidentified specimens have high similarity with S. leucophyla and lies in the same clade. The phylogenetic tree constructed by Maximum Likelihood analysis. The result showed that the monophyletic of Smilacaceae consisted of four clades. The genus Heterosmilax nested with Smilax though with low bootstraps value. It supports the monogeneric status of Smilacaceae.